A DISCRIMINATION TRAINING PROCEDURE TO ESTABLISH CONDITIONED REINFORCERS FOR CHILDREN WITH AUTISM1. (12th March 2014) - Taylor‐Santa, Catherine; Sidener, Tina M.; Carr, James E.; Reeve, Kenneth F.
<x xml:space="preserve">Abstract</x> Although conditioned reinforcers are used in many behavioral intervention programs for individuals with developmental disabilities, little research has been conducted to determine optimal methods for establishing conditioned reinforcers. An early method that has received relatively little research attention is to condition a neutral stimulus as a discriminative stimulus and then use the stimulus as a programed consequence during skill acquisition. The current study evaluated the effects of a discrimination training procedure on establishing conditioned reinforcers for three children with autism. For all participants, previously neutral stimuli reinforced behaviors after acquiring discriminative properties during discrimination training. Copyright © 2014 John Wiley & Sons, Ltd.